LEARNING STYLE VARIATION OF DIGITAL NATIVES - Lai, Yin Ling; Lee, Joseph (PEOPLE: International Journal of Social Sciences, 2019)
Everyone learns, but not all learn in the same way. Understanding of an individual's natural or habitual pattern of processing information, acquiring knowledge and solving problems is considered to be beneficial in developing pedagogical process and enhancing effective learning.This study reviews the impacts of gender, cultural differences, and variations in disciplines to learning styles. With the aim to investigating the learning style variability, 955 students from the "digital native" generation studying at various institutions of higher learning in Malaysia, China, and Indonesia responded to the Felder-Silverman Index of Learning Styles (ILS) and a demographics questionnaire. It is found that gender does not affect the learning style of the students. All students of three nationalities appear to be visual learners. However, Malaysian and Chinese students prefer sensing and sequential learning while the Indonesian students prefer otherwise. Both engineering and business students appear to be similar type of learners except that engineering students are more sequential than the business students. Cultural and disciplinary variation do affect the way students in the digital era prefer to learn.